CHALLENGES ON LEARNING ENGLISH VOCABULARY FACED BY STUDENTS - Fasaaro Hulu; Tisrin Maulina Dewi; Dirneti; Fitria Meilina (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this studies is to explain the challenges faced by grade 10 students at SMK Yos Anugrah Batam. This studies applies a qualitative method using words, sentences and text to explain the research data. The data collection instrument used a closed questionaire. The results of the studies are explained using the choice criteria for vocabulary mastery by category; excellent, better and poor and for vocabulary development applying selection criteria; always, often and never. The results of this study indicate that participants face challenges in mastering English vocabulary, namely lack of understanding all the meanings of vocabulary in each topic studied, lack of understanding conversations because vocabulary less, lact of getting used to read English texts, no having enough time to study, lack of motivation to learn, do not have friends as friends to talk to and do not use English outside of school.